A network pharmacology study on mechanism of resveratrol in treating preeclampsia via regulation of AGE-RAGE and HIF-1 signalling pathways - Shi, Jiamiao; Wang, Jiahao; Jia, Ning; Sun, Qinru (Frontiers in Endocrinology, 2023)
Background Preeclampsia (PE) is a hypertensive disorder of pregnancy that threatens the lives of millions of pregnant women and their babies worldwide. Without effective medications, there are thousands of maternal and child mortalities every year. Resveratrol (RSV), a non-flavonoid polyphenol extracted from multiple plants, has shown positive effects in treating hypertension, cardiovascular disorders, and even PE. This study aimed to explore the pharmacological mechanism of RSV in treating PE by using network pharmacology and bioinformatics. Methods With the use of multiple databases, 66 intersecting targets were obtained from the 347 putative targets of RSV and 526 PE-related genes. Then, Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were conducted to investigate the functions of the intersecting targets. The protein–protein interaction network and target–pathway network were drawn and analyzed to illustrate the correlation between targets and pathways. Finally, molecular docking was conducted to calculate the binding energy between RSV and core targets. Results The results showed that the core targets of RSV were IL6, TNF, IL1B, VEGFA, STAT3, and EGFR. There existed good binding between RSV and IL6, TNF, IL1B, VEGFA, and EGFR. In addition, we found that RSV mainly functioned in the AGE-RAGE and HIF-1 signaling pathways, which are associated with the occurrence and development of PE. Conclusion In conclusion, our findings indicated that RSV has the effects of regulating angiogenesis and anti-inflammation and can be a candidate medicine for treating PE.